Testbed Application of Energy Agents - Loose, Nils; Derksen, Christian; Unland, Rainer (Smart Energy Research. At the Crossroads of Engineering, Economics, and Computer Science. 3rd and 4th IFIP TC 12 International Conferences, SmartER Europe 2016 and 2017, Essen, Germany, February 16-18, 2016, and February 9, 2017, Revised Selected Papers, 2017)
This work introduces the concept of testbed application of energy agents, which is the intermediate step between testing agents in pure simulation environment and deploying them in real energy distribution systems. In the testbed application case, the energy agent is taken from the simulation environment and deployed to dedicated hardware, where it controls a simulated or real technical system, while still working against a simulated environment. Compared to a pure simulation environment, this application case raises a number of new challenges, mainly resulting from inter-platform agent communication. In this work these challenges are discussed and an implementation handling them is presented and evaluated.